Acute Effects of a Glucagon-Like Peptide 2 Analogue, Teduglutide, on Gastrointestinal Motor Function and Permeability in Adult Patients With Short Bowel Syndrome on Home Parenteral Nutrition. (November 2016) - Iturrino, Johanna; Camilleri, Michael; Acosta, Andres; O'Neill, Jessica; Burton, Duane; Edakkanambeth Varayil, Jithinraj; Carlson, Paula J.; Zinsmeister, Alan R.; Hurt, Ryan
Background: Glucagon-like peptide 2 (GLP-2) agonists decrease the need for parenteral nutrition (PN) in short bowel syndrome (SBS); mechanisms evaluated to date have focused on the intestinotrophic effect of GLP-2 agonists such as increased absorptive capacity of the remnant intestine and increased citrulline levels. Other mechanisms may also play a role in effects of GLP-2 agonists. Aim : To measure effects of a GLP-2 agonist, teduglutide (TED), compared with placebo (PLA) on gastric emptying (GE), overall gut transit, fluid balance, intestinal monosaccharide absorption, and permeability in patients with SBS on home PN (HPN). Materials and Methods : In 8 adults with SBS on HPN, we compared daily subcutaneous TED (0.05 mg/kg) and PLA (crossover design, each treatment 7 days with a 14-day washout) on gut transit, intestinal absorption, and permeability after oral mannitol (200 mg) and lactulose (1 g), as well as stool weight and urine volume over 8 hours. Analysis used the paired t test. Results : Of 8 patients, 4 were men, with a mean ± SD age of 54 ± 1 years, body mass index of 25 ± 4 kg/m 2, residual small intestine of 63 ± 12 cm, and 25% ± 15% of residual colon. The overall gut transit (% emptied at 6 hours) was 53.4% ± 15% for TED vs 62.4% ± 15.2% for PLA ( P = .075), with no effect on GE ( P = .74). TED increased urine mannitol excretion at 0–2 hours (16.2 ± 3.6 mg TED vs 11.3 ± 2.2 mg PLA, P = .20) and 0–8 hours (32.7 ± 5.9 mg PLA vs 48.8 ± 8.9 mg TED, P = .17). There were no differences in urine lactulose excretion or lactulose/mannitol ratio (0.024 ± 0.005 TED vs 0.021 ± 0.005 PLA). Over 8 hours, TED (vs PLA) numerically reduced stool weight (mean ± SEM, 77 ± 18 g TED vs 106 ± 43 g PLA, P = .42) and increased urine volume (408.9 ± 52.2 mL TED vs 365.7 ± 57.3 mL PLA, P = .34). Conclusion : Seven-day TED treatment in 8 participants suggests beneficial effects on fluid balance and monosaccharide absorption, and it retarded overall gut transit with no effects on GE or mucosal permeability. Larger, longer, mechanistic studies of TED in SBS are warranted. This trial was registered at clinicaltrials.gov as NCT02099084.